Clinical significance of plasma candidate biomarkers of Alzheimer’s Disease - Lewczuk, Piotr; Łukaszewicz-Zając, Marta; Kornhuber, Johannes; Mroczko, Barbara (Neurologia I Neurochirurgia Polska, 2024)
The number of patients with Alzheimer’s Disease (AD) has increased rapidly in recent decades. AD is a complex progressive neurodegenerative disease affecting c.14 million patients in Europe and the United States. The hallmarks of this disease are neurotic plaques composed of the amyloid-β (Aβ) peptide and neurofibrillary tangles formed of hyperphosphorylated tau protein (pTau). To date, four CSF biomarkers: amyloid beta 42 (Aβ42), Aβ42/40 ratio, Tau protein, and Tau phosphorylated at threonine 181 (pTau181) have been validated as core neurochemical AD biomarkers. Imaging biomarkers are valuable for AD diagnosis, although they suffer from limitations in their cost and accessibility, while CSF biomarkers require lumbar puncture. Thus, there is an urgent need for alternative, less invasive and more cost-effective biomarkers capable of diagnosing and monitoring AD progression in a clinical context, as well as expediting the development of new therapeutic strategies. This review assesses the potential clinical significance of plasma candidate biomarkers in AD diagnosis. We conclude that these proteins might hold great promise in identifying the pathological features of AD. However, the future implementation process, and validation of the assays’ accuracy using predefined cut-offs across more diverse patient populations, are crucial in establishing their utility in daily practice.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Alzheimer’s Disease; amyloid beta; plasma biomarkers; tau